2018
DOI: 10.1016/j.jadohealth.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Medical Home Care for Adolescents in Need of Mental Health Treatment

Abstract: Increasing care accessibility, integrating MH services into primary care settings, and targeting socioeconomically disadvantaged subgroups could improve rates of PCMH care among adolescents with MH needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Although there are no HPC projects within primary care, patient-centered medical homes within primary care assist with the coordination of medical care and increasingly provide direct treatment for MHC, such as anxiety and depression (Asarnow et al, 2017 ). However, research has found that when compared with adolescents without an MHC, those with an MHC are less likely to receive care in a patient-centered medical home (Yonek et al, 2018 ). For youth with multiple mental health comorbidities who are interfacing with several systems simultaneously or sequentially, increased research is needed to determine which settings are best suited to deliver opioid misuse and OUD prevention interventions, the optimal way to deliver these interventions (synchronous in-person or virtual, asynchronous, or independent of an interventionist), as well as what setting should serve as a medical “home” to monitor their response to these interventions over time.…”
Section: Future Directionsmentioning
confidence: 99%
“…Although there are no HPC projects within primary care, patient-centered medical homes within primary care assist with the coordination of medical care and increasingly provide direct treatment for MHC, such as anxiety and depression (Asarnow et al, 2017 ). However, research has found that when compared with adolescents without an MHC, those with an MHC are less likely to receive care in a patient-centered medical home (Yonek et al, 2018 ). For youth with multiple mental health comorbidities who are interfacing with several systems simultaneously or sequentially, increased research is needed to determine which settings are best suited to deliver opioid misuse and OUD prevention interventions, the optimal way to deliver these interventions (synchronous in-person or virtual, asynchronous, or independent of an interventionist), as well as what setting should serve as a medical “home” to monitor their response to these interventions over time.…”
Section: Future Directionsmentioning
confidence: 99%
“…It is unlikely that all children with MH problems require care coordination. Rather, those in highest need should be identified and a coordinated response should be enacted, which has not been the case even in areas where care consistent with a health home model has been implemented (Yonek, Jordan, Dunlop, Ballard, & Holl, 2018). Many children with mild disorders are effectively cared for solely in PHC (Rushton, Bruckman, & Kelleher, 2002).…”
Section: Résumémentioning
confidence: 99%